Arabidopsis thaliana PAD4 encodes a lipase-like gene that is important for salicylic acid signaling - Jirage, Dayadevi (The National Academy of Sciences, 1999)
The Arabidopsis PAD4 gene previously was found to be required for expression of multiple defense responses including camalexin synthesis and PR-1 gene expression in response to infection by the bacterial pathogen Pseudomonas syringae pv. maculicola. This report describes the isolation of PAD4. The predicted PAD4 protein sequence displays similarity to triacyl glycerol lipases and other esterases. The PAD4 transcript was found to accumulate after P. syringae infection or treatment with salicylic acid (SA). PAD4 transcript levels were very low in infected pad4 mutants. Treatment with SA induced expression of PAD4 mRNA in pad4–1, pad4–3, and pad4–4 plants but not in pad4–2 plants. Induction of PAD4 expression by P. syringae was independent of the regulatory factor NPR1 but induction by SA was NPR1-dependent. Taken together with the previous observation that pad4 mutants have a defect in accumulation of SA upon pathogen infection, these results suggest that PAD4 participates in a positive regulatory loop that increases SA levels, thereby activating SA-dependent defense responses.